Effects on ALT normalization in the first month of treatment by Sofosbuvir/Ribavirin therapy versus Sofosbuvir/Daclatasvir therapy in HCV infected individuals - Kashif Rauf, Tehmina Qamar,Bashir Ahmad, Shoaib Malik, Nadeem Naseem, Naseer ud Din, Kashif Rauf, Tehmina Qamar,Bashir Ahmad, Shoaib Malik, Nadeem Naseem, Naseer ud Din (Journal of Rawalpindi Medical College, 2019)
Objective: To evaluate the effects on ALT normalization in first month by SOFOS/RIB therapy versus SOFOS/DAC therapy in HCV infected individuals in Pakistan Study Design: Cross sectional comparative study Material and Methods: In a cross sectional analysis in a total of 200 Hepatitis c infected patients, sex, H/O diabetes mellitus, prior interferon therapy, decrease in hemoglobin >2 gm/dl in 1st month and rise in serum bilirubin in 1st month were the qualitative variables and the quantitative variables were age, weight, baseline hemoglobin, baseline bilirubin at week 4 of treatment. The statistical relation of the mentioned variables was checked using SPSS version 15 on the basis of data collected. Results: Out of total 200 patients, 47% (94) were males, 53% (106) were females, 28% (56) patients were diabetic & 44.5% (89) patients had history of prior interferon therapy, 28.5% (57) patients were having low hemoglobin levels before starting above mentioned treatment. Both the groups completed the treatments A & B for 24 &12 weeks respectively & collected data showed the superiority of treatment B to treatment A as no decrease in hemoglobin (p=0.000), & no rise in serum bilirubin(p=0.000) during 1st month of treatment while ,serum bilirubin was 93 % in treatment B and 73 % in treatment A. Conclusion: The results concluded that treatment B (Sofosbuvir / Daclatasvir for 12 weeks) is superior anti hepatitis C therapy as compared to the treatment A (Sofosbuvir / Ribavirin for 24 weeks) in order to achieve ALT normalization in first month of therapy in Pakistani population. Ribavirin should be avoided to prevent hemolytic anemia as well. Keywords: Hepatitis C, Alkaline Phosphatase